Algae and building façade revisited. a study of façade system for infill design. Issue 4 (2nd October 2017) - Martokusumo, Widjaja; Koerniawan, M. Donny; Poerbo, Heru W.; Ardiani, Nissa A.; Krisanti, Susan H.
Abstract: Buildings account for around 30 percent of the world's total energy consumption and a similar percentage of the world's greenhouse gas emissions the main cause of climate change. The building sector is a major energy consumer, and empirical research reveals that carbon-dioxide emissions from the building sector exceed those of the industry and transport sectors. Contextual juxtaposition has commonly been applied in designing a new building in the historic district. In the realm of design, such philosophy-based design approach requires objective measurements. When new glass building considered, the question on greenhouse gas emissions becomes significant. To minimize energy consumption and reduce sun glare, brise-soleil and horizontal fixed shading devices have been used as elements of building's façade. Nowadays, algae as part of building façade system have been used in creating a healthier indoor environment. This paper is written based on an on-going architectural design-based research on the use and role of algae as part of the building façade system. The new building of ITB Innovation Park is used as an infill project. With the help of modelling and extensive literature survey, this research will investigate how far the building (façade) design is affected by considerations on energy consumption pattern and environmental condition.